Microsatellite instability affecting the T17 repeats in intron 8 of HSP110, as well as five mononucleotide repeats in patients with colorectal carcinoma. (August 2013) - Markovic, Srdjan; Antic, Jadranka; Dimitrijevic, Ivan; Zogovic, Branimir; Bojic, Daniela; Svorcan, Petar; Markovic, Velimir; Krivokapic, Zoran
Aim: To investigate mononucleotide markers: BAT-25, BAT-26, NR-21, NR-22 and NR-24 in patients with colorectal cancer (CRC), and the status of HSP110T17, KRAS, BRAF and the MLH1 promoter mutations in microsatellite unstable CRC.Methods: Genetic assessments were performed on samples obtained following resection of CRC in 200 patients.Results: Allelic variations of HSP110T17 were found in all 18 patients with microsatellite instabilities (MSIs) in at least three markers (high-frequency MSI). By contrast, mutations of HSP110T17 were absent in all 20 patients with no MSI frequency. Eight out of 182 patients with low (instability in one marker) or no frequency MSI had allelic shifts due to polymorphisms of BAT-25 (1.5%), NR-21 (1.75%) and NR-24 (1.5%). BRAF mutations were associated with >5 bp shortening of HSP110T17 .Conclusion: Patients with high-frequency MSI CRC had allelic variations of HSP110T17 . BRAF mutations occur along with greater shortening in HSP110T17 during oncogenesis via the MSI pathway.